PFAS-free degradable tabletop game packaging paper plastic material and preparation method thereof
By using a composite structure of plant fiber paper base and cured impregnated phase in the packaging material of board games, a cross-linked network is formed, which solves the problems of insufficient heat resistance and stability of the material and achieves efficient environmental degradation and performance improvement.
Patent Information
- Application Number
- CN202611237901.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-11-06
AI Technical Summary
Existing board game packaging materials are insufficient in terms of heat resistance and stability, and fluorinated oil repellents have environmental persistence issues. Polyolefin coatings affect paper fiber recycling and environmental degradation, and simple surface coatings cannot fully enhance the fiber network in the thickness direction of the material.
The composite structure of plant fiber paper base and solidified impregnation phase is adopted. A cross-linking network is formed by epoxidized vegetable oil, polyamine compounds and reactive organic modified montmorillonite to enhance the thermomechanical modulus and interfacial bonding of the material, and avoid the use of fluorinated polymers.
It improves the glass transition temperature, thermal decomposition initiation temperature and short-term thermal dimensional stability of the material, reduces water absorption and hygrothermal warping, balances dimensional stability and crack resistance, and achieves environmental degradability.
Smart Images

Figure CN123043800A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmentally degradable materials, paper-based composite materials and packaging materials manufacturing technology, specifically to a PFAS-free biodegradable paper-plastic packaging material for board games and its preparation method. Background Technology
[0002] Board game packaging typically includes an outer box, inner tray, dividers, cards, and accessory supports. These components must maintain dimensional stability during printing, die-cutting, hot pressing, transportation, and long-term storage, and must withstand short-term temperature increases, high humidity, repeated opening and closing, and localized pressure. Existing pulp molding or high-basis-weight paperboard mainly relies on fiber hydrogen bonds to maintain strength, which decreases when exposed to moisture. Commonly used thermoplastic coatings, wax layers, or water-soluble polymer coatings are prone to softening, migration, moisture absorption, or interfacial peeling during heat and moisture cycling.
[0003] To achieve oil-repellent, water-repellent, or barrier properties, existing solutions utilize fluorinated oil repellents, polyolefin coatings, acrylic coatings, polyvinyl alcohol coatings, or wax layers. PFAS-containing systems present environmental durability issues; polyolefin coatings affect paper fiber recycling and environmental degradation; and simple surface coatings cannot adequately reinforce the fiber network in the thickness direction of the material. Chinese invention patent application CN110528332A discloses a high-performance fluorinated oil-repellent paper, which formulates a water-based oil repellent agent from polyvinyl alcohol, a reinforcing agent, and triethyl citrate, and then applies it at a concentration of 0.8–2 g / m³. 2 The coating is applied to the surface of the base paper and dried. This method avoids fluorinated oil repellents, but its functional layers are mainly located on the paper surface and do not build a continuous cross-linked backbone inside the paper fibers; the polyvinyl alcohol phase may still absorb water and plasticize in high humidity environments, thus offering limited improvement on the heat resistance, dimensional stability, and thickness direction bonding of thick cardboard or molded inserts. Chinese invention patent application CN113638267A discloses a biodegradable coated high-barrier paper, which sequentially comprises an acrylic coating, a polyvinyl alcohol-organomontmorillonite coating, and a beeswax coating, each layer dried at 50℃~60℃. This method achieves barrier properties through multi-layer surface coating, but the multi-layer interfaces and the wax phase may still soften, migrate, or mismatch at the interface during thermal and humid cycling.
[0004] Therefore, developing a PFAS-free biodegradable paper-plastic material for board game packaging and its preparation method is of great practical significance. Summary of the Invention
[0005] This invention aims to solve the technical problems of insufficient heat resistance and poor stability in existing technologies. It provides a PFAS-free biodegradable paper-plastic material for tabletop game packaging and its preparation method.
[0006] A PFAS-free biodegradable paper-plastic material for board game packaging and its preparation method are disclosed below:
[0007] The material comprises a plant fiber paper base and a cured impregnated phase; the cured impregnated phase is distributed along the thickness direction of the plant fiber paper base on the fiber surface and in the inter-fiber pores, and the oven-dry weight gain of the composite board relative to the plant fiber paper base is 22%–28%; the non-volatile raw materials used to form the cured impregnated phase, based on 100 parts of the oven-dry weight of the plant fiber paper base, include 17–24 parts of epoxidized vegetable oil, 2.4–3.0 parts of a polyamine compound composed of 2,5-bis(aminomethyl)furan and 1,5-pentanediamine, 0.5–0.6 parts of free ε-poly-L-lysine, 1–5 parts of reactive organic modified montmorillonite, and 0.1–0.2 parts of transesterification catalyst. The reactive organic modified montmorillonite is obtained by sequentially treating sodium montmorillonite with Nε-lauroyl-L-lysine lactate and ε-poly-L-lysine, and has accessible amino groups that can participate in the epoxy ring-opening reaction; the epoxy groups of the epoxidized vegetable oil undergo a ring-opening reaction with the small molecule diamine, the free ε-poly-L-lysine, and the accessible amino groups of the reactive organic modified montmorillonite to form a cross-linked network containing β-hydroxyamine structure and vegetable oil triglyceride ester bonds, and the cross-linked network has the structural conditions for hydroxyl / ester bond exchange under the action of the ester exchange catalyst; no fluorinated polymers, fluorinated surfactants, or fluorinated processing aids are actively added to the raw materials for preparing the composite board.
[0008] Furthermore, the plant fiber paper base is composed of 55% bagasse pulp, 35% bamboo pulp, and 10% microfibrillated cellulose, with a basis weight of 400 g / m³. 2 Thickness 0.75±0.03mm, open porosity 52±3%.
[0009] Furthermore, the epoxidized vegetable oil is a mixture of epoxidized flaxseed oil and epoxidized soybean oil in a mass ratio of 4:1 to 4:6.
[0010] Furthermore, the polyamine compound comprises 1.5 to 2 parts of 2,5-bis(aminomethyl)furan and 0.9 to 1 part of 1,5-pentanediamine.
[0011] Furthermore, the transesterification catalyst is selected from zinc acetate dihydrate or zinc lactate.
[0012] S1: Preparation of montmorillonite dispersion; Nε-lauroyl-L-lysine and 90% lactic acid were added to a mixture of ethanol and water in a 3:1 mass ratio and stirred at 50°C until homogeneous to form a lactate solution. This solution was added dropwise to the montmorillonite dispersion over 30 min and reacted at 50°C and 600 r / min for 2 h. ε-poly-L-lysine and 90% lactic acid were dissolved in water and added to the aforementioned system over 20 min at 40°C. The reaction was continued for 1 h. The mixture was centrifuged at 3000-4000 r / min for 10-15 min, washed three times with ethanol, and then washed once with deionized water. The precipitate was vacuum dried at 45°C and -0.090 MPa to constant weight, pulverized, and passed through a 325 mesh sieve to obtain reactive organic modified montmorillonite.
[0013] S2: Epoxidized vegetable oil and ethyl lactate were mixed at 35°C and 400–500 r / min for 10–20 min to obtain an oil phase. Water, ethanol, alkyl polysaccharide APG0810, free ε-poly-L-lysine, and transesterification catalyst were mixed, and reactive organic modified montmorillonite was added. The mixture was dispersed at 8000–10000 r / min for 5–15 min, and then sonicated at 200–300 W for 2–3 min to obtain an aqueous dispersion. A polyamine compound was added to the oil phase and mixed at 600–800 r / min for 2–6 min, with an epoxy equivalent / amine active hydrogen equivalent of 1.04. Subsequently, the aqueous dispersion was added to the oil phase within 8 min, while simultaneously dispersing at 12000 r / min. After the addition was completed, a pre-reaction was carried out, and then the mixture was cooled to 25°C to obtain a prepolymer with a viscosity of 350–580 mPa·s at 25°C.
[0014] S3: The plant fiber paper base is conditioned at 23℃ and 65%RH to achieve a moisture content of 8% to 15%. Then, it is vacuum impregnated. The paper base is removed and passed through a double roller once with a linear pressure of 0.2 to 0.8 MPa and a speed of 2 m / min. It is weighed and the final oven-dry weight gain is adjusted by adjusting the roller gap to achieve a final oven-dry weight gain of 22% to 28%, thus obtaining impregnated paper.
[0015] S4: The impregnated paper after squeezing out the liquid is laid flat in a pre-drying equipment with solvent recovery and explosion-proof ventilation structure, and pre-dried at 60±5℃ and gauge pressure -0.060MPa. It is weighed every 5 minutes until the mass change does not exceed 0.5% for 5 consecutive minutes. Then the impregnated paper base is placed in a glass-ceramic pressing mold and subjected to microwave radiation. Then it is humidified at 23℃ and 50%RH for 48 hours to obtain the paper-plastic material for tabletop game packaging.
[0016] Further, the preparation of montmorillonite dispersion in step S1 specifically involves adding sodium montmorillonite to deionized water, stirring at 600-800 r / min for 45-65 min, sonicating at 20 kHz, 450 W, 5s on / 5s off for 15 min, and keeping the system below 35°C to obtain montmorillonite dispersion.
[0017] Furthermore, the pre-reaction described in step S2 specifically involves a pre-reaction at 40–50°C and 500–600 r / min for 10–20 min.
[0018] Further, the vacuum impregnation described in step S3 specifically involves completely immersing the paper base in the prepolymer and vacuum impregnating it for 2 to 8 minutes under a gauge pressure of -0.060 to -0.095 MPa; then restoring it to normal pressure within 30 to 90 seconds and continuing to soak it for 1 to 5 minutes.
[0019] Further, the microwave radiation described in step S4 specifically involves applying a surface pressure of 0.5–1.5 MPa, performing pulse radiation with 2.45 GHz microwaves in 12-second on / 8-second off cycles, achieving an effective absorption power density of 0.8–1.2 W / g, accumulating on for 180–300 seconds, maintaining a core temperature of 110–120°C, and ensuring the temperature difference between the core and surface is no greater than 15°C. After stopping the microwave, the pressure is maintained for 3 minutes, and the core is demolded after the temperature drops below 70°C.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention restricts the movement of vegetable oil network segments and paper fiber microregions through reactive nanosheets, thereby improving the glass transition temperature, thermal decomposition initiation temperature and short-term thermal dimensional stability; the higher epoxy functionality of epoxidized linseed oil and the rigidity of furan cyclodiamine improve the crosslinking density; epoxidized soybean oil and 1,5-pentanediamine provide flexibility and reduce brittleness.
[0022] (2) In this invention, the polyamino group of ε-poly-L-lysine forms hydrogen bonds with the hydroxyl group of the fiber and participates in the ring opening of the epoxy, thereby improving the wet interface bonding; the nanosheets form a tortuous diffusion path, reducing water absorption and humid heat warping; the dynamic ester exchange relaxes the local residual stress during the high temperature stage of curing and maintains a low exchange rate during the room temperature storage stage, thus taking into account both dimensional stability and crack resistance. Attached Figure Description
[0023] Figure 1 This is a three-dimensional deformation cloud map for Experiment Example 2.
[0024] Figure 2 The load retention rate diagram is for Experiment Example 3. Detailed Implementation
[0025] The following embodiments further explain and illustrate the technical solutions of the present invention. It is particularly noted that each specific embodiment is a specific interpretation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention. A PFAS-free biodegradable paper-plastic material for board game packaging and its preparation method are detailed in the following steps:
[0026] 1. Preparation of reactive organic-modified montmorillonite
[0027] Sodium-type montmorillonite contains exchangeable cations in its interlayer. Unmodified, it is highly hydrophilic and readily aggregates in vegetable oil phases. Nε-lauroyl-L-lysine contains a C12 fatty chain, a carboxyl group, and a protonable α-amino group. After forming a salt with lactic acid, the cationic amino group enters the interlayer and replaces some of the Na+. + The aliphatic chains reduce the surface energy of the sheets, while the retained amino groups can react with epoxy groups subsequently. ε-poly-L-lysine contains multiple free α-amino groups, which can form multi-point electrostatic adsorption, hydrogen bonds, and bridging at the edges of the sheets and between the expanded layers. The high aspect ratio of the layered silicate nanosheets extends the diffusion path of water and small molecules; their confinement effect on fiber and network segments increases the thermomechanical modulus. After the amino groups participate in crosslinking, the interfacial shearing changes from physical friction to covalent bonding and multi-point hydrogen bonding, reducing sheet slip and interfacial voids during thermal and humid cycling.
[0028] 2. Preparation of crosslinked prepolymer mixture
[0029] Epoxidized linseed oil, with its high epoxy functionality, is used to improve crosslinking density and heat resistance; epoxidized soybean oil, with its long, flexible fatty acid chains, is used to reduce brittleness. The furan ring of 2,5-bis(aminomethyl)furan increases segment rigidity and glass transition temperature; the flexible carbon chain of 1,5-pentanediamine reduces prepolymer viscosity and improves fiber wetting; ε-poly-L-lysine provides multifunctional reaction sites and interfacial affinity with cellulose.
[0030] 3. Vacuum impregnation
[0031] Plant fiber paper base is conditioned at 23°C and 65%RH, and the paper base is completely immersed in the prepolymer and vacuum impregnated; it is weighed by passing it through two rollers and the roller gap is adjusted to make the final oven-dry weight gain rate 22% to 28%, thus obtaining impregnated paper.
[0032] 4. Microwave in-situ curing
[0033] The impregnated paper after solvent extraction is laid flat in a pre-drying device with solvent recovery and explosion-proof ventilation structure, and pre-dried at 60±5℃ and gauge pressure -0.060MPa. It is weighed every 5 minutes until the mass change does not exceed 0.5% for 5 consecutive minutes. Then the impregnated paper base is placed in a glass-ceramic pressing mold, and a surface pressure of 0.5~1.5MPa is applied. Pulse radiation with 2.45GHz microwave is applied for 12s on and 8s off, with an effective absorption power density of 0.8~1.2W / g. The cumulative on time is 180~300s, the core temperature is 110℃~120℃, and the pressure is maintained for 3 minutes after the core stops microwave. The paper is then demolded and humidified to obtain the paper-plastic material for tabletop game packaging.
[0034] Example 1
[0035] Table 1 Raw Material Information Table
[0036] Raw material name Model / Dosage Form CAS number Sodium montmorillonite CEC 95 meq / 100g; D50 8μm 1318-93-0 Nε-lauroyl-L-lysine Purity ≥ 98%; Mw 328.49 52315-75-0 lactic acid Quality score 90% 50-21-5 ethanol Purity ≥ 99.5% 64-17-5 ε-poly-L-lysine Purity ≥ 95%; Mw 3.5~4.5kDa 28211-04-3 Epoxidized flaxseed oil Epoxy oxygen content 9.0%; acid value ≤ 1.0 mg KOH / g 8016-11-3 Epoxidized soybean oil Epoxy oxygen content 6.5%; acid value ≤0.8mgKOH / g 8013-07-8 Ethyl lactate Purity ≥ 99% 97-64-3 Alkyl polysaccharide APG0810 Active ingredient ≥50% 68515-73-1 Zinc acetate dihydrate Purity ≥ 98%; Mw 219.50 5970-45-6 2,5-Bis(aminomethyl)furan Purity ≥ 98%; Mw 126.16 2213-51-6 1,5-Pentanediamine Purity ≥ 98%; Mw 102.18 462-94-2 Plant fiber paper base The paper base is composed of 55% bagasse pulp, 35% bamboo pulp, and 10% microfibrillated cellulose, with a basis weight of 400 g / m², a thickness of 0.75 ± 0.03 mm, and an open porosity of 52 ± 3%. -
[0037] S1: Add 3 parts of sodium montmorillonite to 140 parts of deionized water and stir at 700 r / min for 55 min; sonicate at 20 kHz, 450 W, 5s on / 5s off for 15 min while keeping the system below 35℃ to obtain a montmorillonite dispersion; add 0.7 parts of Nε-lauroyl-L-lysine and 0.2 parts of 90% lactic acid to 40 parts of a mixture of ethanol and water in a 3:1 mass ratio, and stir at 50℃ until homogeneous to form a lactate solution. This solution is then added dropwise to the montmorillonite solution over 30 min. In the de-modified montmorillonite dispersion, the reaction was carried out at 50℃ and 600r / min for 2h. 0.2 parts of ε-poly-L-lysine and 0.05 parts of 90% lactic acid were dissolved in 20 parts of water and added to the above system at 40℃ over 20min. The reaction was continued for 1h. The mixture was centrifuged at 3500r / min for 12min, washed three times with ethanol, and then washed once with deionized water. The precipitate was vacuum dried at 45℃ and -0.090MPa to constant weight, pulverized and passed through a 325-mesh sieve to obtain reactive organic modified montmorillonite.
[0038] S2: 21 parts of epoxidized vegetable oil (a mixture of epoxidized linseed oil and epoxidized soybean oil in a 4:3 mass ratio) and 8 parts of ethyl lactate were mixed at 35℃ and 450 r / min for 15 min to obtain the oil phase. 35 parts of water, 8 parts of ethanol, 0.25 parts of alkyl polysaccharide APG0810, 0.55 parts of ε-poly-L-lysine, and 0.15 parts of zinc acetate dihydrate (a transesterification catalyst) were mixed. 3 parts of reactive organic-modified montmorillonite from step 1 were added, and the mixture was dispersed at 9000 r / min for 10 min, followed by ultrasonication at 250 W for 2.5 min to obtain the final product. The aqueous dispersion was then added to the oil phase. The polyamine compound contained 1.8 parts of 2,5-bis(aminomethyl)furan and 0.95 parts of 1,5-pentanediamine. The mixture was stirred at 700 r / min for 4 min, and the epoxy equivalent / amine active hydrogen equivalent was approximately 1.04 (excluding the amino groups on the modified montmorillonite). Subsequently, the aqueous dispersion was added to the oil phase over 8 min, while simultaneously dispersing at 12000 r / min. After the addition was completed, the mixture was pre-reacted at 45 °C and 550 r / min for 15 min, and then cooled to 25 °C to obtain the prepolymer, which had a viscosity of 475 mPa·s at 25 °C.
[0039] S3: 100 parts of plant fiber paper base are conditioned at 23℃ and 65%RH to achieve a moisture content of 11%. The paper base is completely immersed in the prepolymer and vacuum impregnated for 5 minutes under a gauge pressure of -0.08MPa. The pressure is restored to normal within 60 seconds, and the paper base is soaked for another 3 minutes. The paper base is then removed and passed through a double roller once at a linear pressure of 0.5MPa and a speed of 2m / min. The paper is weighed and the roller gap is adjusted to achieve a final oven-dry weight gain of 25%, thus obtaining impregnated paper.
[0040] S4: The impregnated paper after extrusion is laid flat in a pre-drying device with solvent recovery and explosion-proof ventilation structure, and pre-dried at 60±5℃ and gauge pressure -0.060MPa. It is weighed every 5 minutes until the mass change does not exceed 0.5% for 5 consecutive minutes. Then the impregnated paper base is placed in a glass-ceramic pressing mold, and a surface pressure of 1MPa is applied. It is then subjected to pulse radiation with 2.45GHz microwave for 12s on and 8s off, with an effective absorption power density of 1W / g. The cumulative on time is 240s, the core temperature is 115℃, and the temperature difference between the core and the surface is not greater than 15℃. After the microwave is stopped, the pressure is maintained for 3 minutes. After the core temperature is lower than 70℃, it is demolded. Then it is humidified at 23℃ and 50%RH for 48 hours to obtain the paper-plastic material for tabletop game packaging.
[0041] Example 2
[0042] The preparation method is the same as in Example 1, but with the following differences:
[0043] In step S1: 1 part of sodium montmorillonite is added to 130 parts of deionized water and stirred at 600 r / min for 65 min; 0.6 parts of Nε-lauroyl-L-lysine and 0.15 parts of 90% lactic acid are added to 35 parts of a mixture of ethanol and water in a 3:1 mass ratio; 0.15 parts of ε-poly-L-lysine and 0.04 parts of 90% lactic acid are dissolved in 20 parts of water and centrifuged at 3000 r / min for 15 min.
[0044] Example 3
[0045] The preparation method is the same as in Example 1, but with the following differences:
[0046] In step S1: 5 parts of sodium montmorillonite were added to 150 parts of deionized water and stirred at 800 r / min for 45 min; 0.8 parts of Nε-lauroyl-L-lysine and 0.25 parts of 90% lactic acid were added to 45 parts of a mixture of ethanol and water in a 3:1 mass ratio; 0.25 parts of ε-poly-L-lysine and 0.06 parts of 90% lactic acid were dissolved in 20 parts of water and centrifuged at 4000 r / min for 10 min.
[0047] Example 4
[0048] The preparation method is the same as in Example 1, but with the following differences:
[0049] In step S2: 17 parts of epoxidized vegetable oil (a mixture of epoxidized linseed oil and epoxidized soybean oil in a 4:1 mass ratio) and 6 parts of ethyl lactate were mixed at 35°C and 400 r / min for 20 min to obtain the oil phase. 30 parts of water, 5 parts of ethanol, 0.2 parts of alkyl polysaccharide APG0810, 0.5 parts of ε-poly-L-lysine, and 0.1 parts of zinc lactate transesterification catalyst were mixed, and 1 part of reactive organic-modified montmorillonite was added. The mixture was dispersed at 8000 r / min for 15 min, and then further dispersed at 2... The mixture was sonicated at 00W for 3 min to obtain an aqueous dispersion. A polyamine compound containing 1.5 parts of 2,5-bis(aminomethyl)furan and 0.9 parts of 1,5-pentanediamine was added to the oil phase and mixed at 600 r / min for 6 min. The aqueous dispersion was then added to the oil phase over 8 min while being dispersed at 12000 r / min. After the addition was completed, the mixture was pre-reacted at 40℃ and 500 r / min for 20 min, and then cooled to 25℃ to obtain a prepolymer with a viscosity of 350 mPa·s at 25℃.
[0050] In step S3: the final dry weight gain was 22%.
[0051] Example 5
[0052] The preparation method is the same as in Example 1, but with the following differences:
[0053] In step S2: 24 parts of epoxidized vegetable oil (a mixture of epoxidized linseed oil and epoxidized soybean oil in a mass ratio of 4:6) and 10 parts of ethyl lactate were mixed at 35℃ and 500 r / min for 10 min to obtain the oil phase. 40 parts of water, 10 parts of ethanol, 0.3 parts of alkyl polysaccharide APG0810, 0.6 parts of ε-poly-L-lysine, and 0.2 parts of transesterification catalyst were mixed, and 5 parts of reactive organic-modified montmorillonite were added. The mixture was dispersed at 10000 r / min for 5 min. An aqueous dispersion was obtained by sonication at 300W for 2 min. A polyamine compound containing 2 parts 2,5-bis(aminomethyl)furan and 1 part 1,5-pentanediamine was added to the oil phase and mixed at 800 r / min for 2 min. The aqueous dispersion was then added to the oil phase over 8 min while being dispersed at 12000 r / min. After the addition was completed, the mixture was pre-reacted at 50℃ and 600 r / min for 10 min, and then cooled to 25℃ to obtain a prepolymer with a viscosity of 580 mPa·s at 25℃.
[0054] In step S3: the final dry weight gain rate is 28%.
[0055] Example 6
[0056] The preparation method is the same as in Example 1, but with the following differences:
[0057] In step S3: the moisture content of the plant fiber paper base reaches 8%, the paper base is completely immersed in the prepolymer, and vacuum impregnates for 8 minutes under a gauge pressure of -0.060MPa; within 30 seconds, the pressure is restored to normal and the paper base is soaked for another 5 minutes. The paper base is then removed and passed through a double roller once at a linear pressure of 0.2MPa and a speed of 2m / min.
[0058] In step S4: 0.5 MPa surface pressure is applied, the effective power density is 0.8 W / g, the cumulative on-time is 300 s, and the core temperature is 110 ℃.
[0059] Example 7
[0060] The preparation method is the same as in Example 1, but with the following differences:
[0061] In step S3: the moisture content of the plant fiber paper base reaches 15%, the paper base is completely immersed in the prepolymer, and vacuum impregnates for 2 minutes under a gauge pressure of -0.095MPa; within 90 seconds, the pressure is restored to normal and the paper base is soaked for another 1 minute. The paper base is then removed and passed through a double roller once at a linear pressure of 0.8MPa and a speed of 2m / min.
[0062] In step S4: 1.5 MPa surface pressure is applied, the effective absorption power density is 1.2 W / g, the cumulative on-time is 180 s, and the core temperature is 120 ℃.
[0063] Comparative Example 1
[0064] The preparation method of Example 1 is followed, but without the addition of reactive organic-modified montmorillonite. All other steps are the same.
[0065] Comparative Example 2
[0066] The preparation method of Example 1 is followed, but unmodified sodium montmorillonite is used instead of reactive organic-modified montmorillonite. All other steps are the same.
[0067] Comparative Example 3
[0068] The preparation method of Example 1 is followed, but without the addition of epoxidized vegetable oil. All other steps are the same.
[0069] Comparative Example 4
[0070] The preparation method of Example 1 was followed, but without the addition of a polyamine compound. All other steps were the same.
[0071] Comparative Example 5
[0072] The preparation method of Example 1 was followed, but without the addition of an transesterification catalyst. All other steps were the same.
[0073] Experimental Example 1
[0074] The comprehensive performance of the paper-plastic packaging materials for board games prepared in Examples 1-7 and Comparative Examples 1-5 was measured.
[0075] Dry tensile strength test: The test was conducted in accordance with the standard GB / T 12914-2018 "Determination of tensile strength of paper and paperboard - constant speed tensile test (20 mm / min)". The specimen was cut into strips 15 mm wide and its tensile strength was determined in a constant speed tensile testing machine at a tensile speed of 20 mm / min.
[0076] Wet strength retention rate: After immersing the sample in deionized water at 25°C for 24 hours, remove it, gently absorb the surface moisture with filter paper, and immediately determine the wet tensile strength using the same test method as for dry tensile strength. Wet strength retention rate = wet tensile strength / dry tensile strength × 100%.
[0077] Heat distortion temperature test: Referring to ASTM D648 "Heat distortion temperature of plastics" standard, the heat distortion temperature of the material is determined by the three-point bending method. The sample is cut into length and width dimensions of 127mm × 13mm. Then, 4-5 layers of the cut sample are neatly stacked and fixed only at both ends with a small amount of quick-drying glue. After curing and trimming, the standard sample is placed on the three-point bending device and heated at a constant rate under a standard load of 0.45MPa. The temperature when the bending deflection of the sample reaches 0.25mm is recorded as the heat distortion temperature.
[0078] Heat-resistant oil performance test: Immerse the sample in edible soybean oil at 120±2℃ for 30 minutes. After removal, observe the appearance of the sample for any delamination, deformation, leakage, or damage. The evaluation grades are as follows: Grade A - No delamination, deformation, or leakage; Grade B - Slight discoloration but no delamination or deformation; Grade C - Obvious delamination or deformation; Grade D - Leakage or damage.
[0079] Water absorption test: Dry the sample in a 50℃ oven to constant weight (m0), then soak it in deionized water at 25℃ for 24 hours. After removal, absorb the surface moisture with filter paper and weigh (m1). Water absorption rate = (m1−m0) / m0 × 100%
[0080] Damp-heat dimensional change rate test: The sample was placed in a constant temperature and humidity chamber at 40℃ and 90% relative humidity for 72 hours. After removal, the dimensional change rate along the length of the sample was measured. Dimensional change rate = (L1−L0) / L0×100%, where L0 is the initial length and L1 is the length after damp-heat aging; positive values indicate expansion and negative values indicate contraction.
[0081] Biodegradation rate test: Referring to the standard GB / T 19277.1-2025 "Determination of final aerobic biodegradation capacity of materials under controlled composting conditions by measuring the released carbon dioxide", the sample was mixed with composting inoculum and placed in a composting container. Composting was carried out under the conditions of temperature 58±2℃ and humidity 50%~55%. The percentage of carbon to carbon dioxide in the sample was measured after 60 days, with cellulose with a particle size of less than 20μm as the reference.
[0082] Total organic fluorine content test: The total organic fluorine content in the sample is determined by combustion ion chromatography. An online combustion-ion chromatography system is used to determine the total organic fluorine content in the sample. This technique combines a high-temperature combustion device with ion chromatography detection. The sample is burned in an oxygen-rich environment at temperatures above 1000℃, converting organic fluorine into absorbable gases such as hydrogen fluoride. After being captured by an absorbent, the gases are qualitatively and quantitatively analyzed by ion chromatography. The detection limit is 1.0 mg / kg; values below the detection limit are reported as not detected.
[0083] The specific test comparison results are shown in Tables 2 and 3:
[0084] Table 2 Comparison of test results for dry tensile strength, wet strength retention, heat distortion temperature, and heat-resistant oil grade of Examples 1-7 and Comparative Examples 1-5
[0085] experimental group Dry tensile strength (MPa) Wet strength retention rate (%) Heat distortion temperature (°C) Heat-resistant oil grade Example 1 138±4 87.3 168±2 A Example 2 133±3 86.9 166±3 A Example 3 132±3 86.8 162±2 A Example 4 134±4 87.2 165±2 A Example 5 137±3 87.3 168±3 A Example 6 136±4 86.5 164±2 A Example 7 135±3 86.9 163±2 A Comparative Example 1 82±4 46.8 98±3 B Comparative Example 2 97±3 74.2 131±2 B Comparative Example 3 56±3 51.1 84±3 D Comparative Example 4 45±2 42.5 77±2 D Comparative Example 5 115±3 77.9 143±3 B
[0086] Table 3. Comparison of test results for water absorption rate, wet heat dimensional change rate, degradation rate, and total organic fluorine content between Examples 1-7 and Comparative Examples 1-5.
[0087] experimental group Water absorption rate (%) Moist heat dimensional change rate (%) Degradation rate (%) Total organic fluorine content (mg / kg) Example 1 7.1 0.48 93.2 Not detected Example 2 8.2 0.51 91.5 Not detected Example 3 8.4 0.52 92.5 Not detected Example 4 8.3 0.48 93.1 Not detected Example 5 7.2 0.49 93.2 Not detected Example 6 7.5 0.50 92.7 Not detected Example 7 7.8 0.51 91.9 Not detected Comparative Example 1 21.2 0.89 91.2 Not detected Comparative Example 2 15.8 0.61 92.8 Not detected Comparative Example 3 28.8 3.11 93.1 Not detected Comparative Example 4 29.0 3.89 92.2 Not detected Comparative Example 5 11.9 0.86 92.5 Not detected
[0088] As can be seen from the above comparison results, no organic fluorine content was detected in any of the examples and comparative examples, and the degradation rate was good. However, in Comparative Example 1 without the addition of reactive organic modified montmorillonite, its dry tensile strength, wet strength retention rate, and heat distortion temperature decreased compared to the examples, its heat-resistant oil grade was B, and its water absorption rate increased. This indicates that reactive organic modified montmorillonite significantly improves material performance through the following mechanisms: the high aspect ratio of the nanosheets forms a "maze effect" to block pathways, effectively inhibiting the diffusion of water molecules, confining the vegetable oil network segments and paper fiber microregions, improving the thermomechanical modulus and heat distortion temperature; the amino groups on the surface of montmorillonite participate in the epoxy ring-opening crosslinking, and the interfacial shearing changes from physical friction to covalent bonding and multi-point hydrogen bonding, significantly improving the interfacial bonding strength. Comparative Example 2 used unmodified sodium montmorillonite instead of reactive organic modified montmorillonite. Its dry tensile strength, wet strength retention, and heat distortion temperature decreased compared to the example, and its heat-resistant oil grade was B. The water absorption rate increased because unmodified sodium montmorillonite is highly hydrophilic and easily aggregates in the vegetable oil phase, making it impossible to achieve uniform dispersion at the nanoscale. Its interlayer spacing is much smaller than that of reactive organic modified montmorillonite, making it difficult for polymer chains to enter the interlayer and form intercalation structures. The sodium montmorillonite surface lacks active amino groups that can participate in cross-linking reactions, preventing the formation of covalent interfaces and providing only limited physical reinforcement. Comparative Example 3 did not add epoxidized vegetable oil. Its dry tensile strength, wet strength retention, and heat distortion temperature decreased compared to the example, and its heat-resistant oil grade was D. It also had a higher water absorption rate and wet-heat dimensional change rate, indicating that epoxidized vegetable oil is the core component for constructing the cross-linked network. Multiple epoxy groups in epoxidized vegetable oil molecules undergo ring-opening addition reactions with the amine groups of polyamine compounds, forming a cross-linked network containing β-hydroxyamine structures and vegetable oil triglyceride ester bonds. This cross-linked network effectively restricts the thermal motion of polymer chain segments, increases the glass transition temperature and heat distortion temperature, enhances interfacial bonding, and improves oil resistance. Comparative Example 4, without the addition of polyamine compounds, showed a decrease in dry tensile strength, wet strength retention, and heat distortion temperature compared to the examples. Its heat resistance oil grade was D, and it exhibited higher water absorption and wet heat dimensional change rate, indicating that the polyamine compound is another core component of the cross-linking reaction. This invention employs a compound system of 2,5-bis(aminomethyl)furan and 1,5-pentanediamine. The furan ring of 2,5-bis(aminomethyl)furan has a rigid structure, which can improve the segmental rigidity and glass transition temperature of the crosslinked network. The flexible carbon chain of 1,5-pentanediamine can reduce the viscosity of the prepolymer and improve the fiber wetting effect. ε-poly-L-lysine provides multifunctional reaction sites, and its polyamino groups form hydrogen bonds with the hydroxyl groups of the fiber and participate in epoxy ring opening, improving the wet interface bonding. The compound of these three components achieves synergistic optimization of rigidity, flexibility, and interfacial affinity.Comparative Example 5, without the addition of a transesterification catalyst, exhibited lower dry tensile strength, wet strength retention, and heat distortion temperature compared to the Example 5. Its heat-resistant oil grade was B, and its water absorption and dimensional change rate were higher. This is because the transesterification catalyst can catalyze the dynamic exchange reaction of amino ester bonds during the high-temperature curing stage, relaxing the local residual stress generated by curing shrinkage in the crosslinked network. The presence of residual stress leads to microscopic defects within the material, reducing mechanical properties and dimensional stability. The dynamic transesterification reaction allows the crosslinked network to achieve local chain segment rearrangement while maintaining overall structural integrity, thus balancing dimensional stability and crack resistance.
[0089] Experimental Example 2
[0090] The finished product prepared in Example 1 is denoted as sample H1, and then samples C1, C2, and C3 are prepared respectively.
[0091] C1: Use the same prepolymer and paper base as H1, but omit vacuum impregnation. Apply the prepolymer evenly to both sides of the paper base in three coats using a doctor blade, slit die, or roller coating method; weigh each coat to achieve a total oven-dry weight gain of 25 ± 1 percentage points. The target ratio for both sides is 50:50, with a single-sided deviation not exceeding 5% of the total weight gain. Subsequently, process under the same pre-drying, die-forming, and microwave curing conditions as H1.
[0092] C2: No prepolymer added. After the paper base is conditioned to a moisture content of 11±1%, it is placed in the same matching mold and isothermally formed under a surface pressure of 1.0MPa. To obtain comparable geometry, hot pressing at 115±3℃ for 400s and holding pressure for 3min can be used, followed by demolding at a temperature below 70℃.
[0093] C3: Except for the absence of 0.15 parts zinc acetate dihydrate in the aqueous phase, the other raw materials, vacuum impregnation, oven-drying weight gain, pre-drying, microwave curing and humidity conditioning conditions are the same as those in H1.
[0094] Four samples were subjected to 3D deformation cloud map testing using a blue light structured light 3D scanner. The single measurement accuracy was ≤0.03mm; spatial resolution ≤0.10mm; repeatability ≤0.05mm. A dual-camera setup was used, with each camera having ≥5 megapixels. Blue light projection was employed, with a working distance of 350±20mm. The testing environment was 23±1℃ and 50±2%RH. The test results are as follows: Figure 1 As shown;
[0095] The H1 cloud map is predominantly green / cyan, with only slight positive and negative displacements at the edges and corners, indicating that the thickness-direction impregnation network, nanosheet confinement, and stress relaxation during the curing stage collectively suppress hygrothermal warping. Although the C1 surface coating exhibits the same oven-dry weight gain, the core layer lacks a continuous cross-linked framework. Under hot and humid conditions, the surface and core layers experience moisture absorption and shrinkage mismatch, resulting in a concave side and an upward warping side. C2 shows the largest displacement among the four groups; the center of the base plate is significantly concave, and the outer edge curls upward, consistent with the expectation of weakened fiber hydrogen bonds, compression creep, and uneven drying shrinkage in unimpregnated paper bases under high humidity. C3 falls between C1 and C2. Without a zinc catalyst, hydroxyl / ester bond exchange and local segment rearrangement are limited during the high-temperature curing stage, and residual stress is released as permanent distortion during hygrothermal cycling.
[0096] Experimental Example 3
[0097] Samples H1 and C1-C3 prepared in Experimental Example 2 were used for compression bearing capacity retention testing. An electronic universal testing machine was used with a 5kN load sensor; accuracy 0.5 or better; sampling frequency ≥50Hz; upper and lower parallel rigid plates were used, with dimensions ≥320mm×240mm, flatness ≤0.05mm, and parallelism deviation ≤0.10mm; preload 2.0N, compression speed 10.0±0.5mm / min, and termination condition being 20% compression of the initial height; the test environment was 23±1℃ and 50±2%RH. Samples were equilibrated in this environment for at least 2 hours before testing. The test results are as follows: Figure 2 As shown;
[0098] After 10 cycles, H1 retained 92.0%, a cumulative decrease of 8.0 percentage points, averaging about 0.8 percentage points per cycle; the curve showed a slow, almost linear decrease, indicating that structural damage and humid heat softening were suppressed. C1 retained 70.0% after 10 cycles, a cumulative decrease of 30 percentage points. With the same weight gain but only surface coating, the surface layer was more prone to microcracks, interfacial peeling, and local buckling under humid heat and repeated contact, resulting in significantly lower load-bearing capacity than H1. C2 retained 62.0% after 10 cycles, the lowest among the four groups; its rate of decrease was approximately 3.8 percentage points per cycle, indicating that the paper base without a cross-linked impregnated phase under high humidity stacking under significant plasticization and crushing. C3 retained 78.0% after 10 cycles, better than C1 and C2 but significantly lower than H1. This ranking is consistent with the mechanism that "residual stress is more difficult to relax when there is no catalyst, and permanent deformation and crack accumulation are faster after cycling."
Claims
1. A PFAS-free biodegradable paper-plastic material for tabletop game packaging, characterized in that, The composite board comprises a plant fiber paper base and a cured impregnated phase; the cured impregnated phase is distributed along the thickness direction of the plant fiber paper base on the fiber surface and in the inter-fiber pores, and the oven-dry weight gain of the composite board relative to the plant fiber paper base is 22%–28%; the non-volatile raw materials used to form the cured impregnated phase, based on 100 parts of the oven-dry weight of the plant fiber paper base, include 17–24 parts of epoxidized vegetable oil, 2.4–3.0 parts of a polyamine compound composed of 2,5-bis(aminomethyl)furan and 1,5-pentanediamine, 0.5–0.6 parts of free ε-poly-L-lysine, 1–5 parts of reactive organic modified montmorillonite, and 0.1–0.2 parts of transesterification catalyst; The reactive organic modified montmorillonite is obtained by sequentially treating sodium montmorillonite with Nε-lauroyl-L-lysine lactate and ε-poly-L-lysine, and has accessible amino groups that can participate in the epoxy ring-opening reaction; the epoxy groups of the epoxidized vegetable oil undergo a ring-opening reaction with the small molecule diamine, the free ε-poly-L-lysine, and the accessible amino groups of the reactive organic modified montmorillonite to form a cross-linked network containing β-hydroxyamine structure and vegetable oil triglyceride ester bonds, and the cross-linked network has the structural conditions for hydroxyl / ester bond exchange under the action of the ester exchange catalyst; no fluorinated polymers, fluorinated surfactants, or fluorinated processing aids are actively added to the raw materials for preparing the composite board.
2. The PFAS-free biodegradable paper-plastic material for tabletop game packaging according to claim 1, characterized in that, The plant fiber paper base is composed of 55% sugarcane residue pulp, 35% bamboo pulp and 10% microfibrillated cellulose, with a basis weight of 400 g / m 2 , a thickness of 0.75±0.03 mm and an open porosity of 52±3%.
3. The PFAS-free biodegradable paper-plastic material for tabletop game packaging according to claim 1, characterized in that, The epoxidized vegetable oil is a mixture of epoxidized flaxseed oil and epoxidized soybean oil in a mass ratio of 4:1 to 4:
6.
4. The PFAS-free biodegradable paper-plastic material for tabletop game packaging according to claim 1, characterized in that, The polyamine compound comprises 1.5 to 2 parts of 2,5-bis(aminomethyl)furan and 0.9 to 1 part of 1,5-pentanediamine.
5. The PFAS-free biodegradable paper-plastic material for tabletop game packaging according to claim 1, characterized in that, The transesterification catalyst is selected from zinc acetate dihydrate or zinc lactate.
6. A method for preparing a PFAS-free biodegradable paper-plastic material for tabletop game packaging according to any one of claims 1-5, characterized in that, Includes the following steps: S1: Preparation of montmorillonite dispersion; Nε-lauroyl-L-lysine and 90% lactic acid were added to a mixture of ethanol and water in a 3:1 mass ratio and stirred at 50°C until homogeneous to form a lactate solution. This solution was added dropwise to the montmorillonite dispersion over 30 min and reacted at 50°C and 600 r / min for 2 h. ε-poly-L-lysine and 90% lactic acid were dissolved in water and added to the aforementioned system over 20 min at 40°C. The reaction was continued for 1 h. The mixture was centrifuged at 3000-4000 r / min for 10-15 min, washed three times with ethanol, and then washed once with deionized water. The precipitate was vacuum dried at 45°C and -0.090 MPa to constant weight, pulverized, and passed through a 325 mesh sieve to obtain reactive organic modified montmorillonite. S2: Epoxidized vegetable oil and ethyl lactate are mixed at 35℃ and 400-500 r / min for 10-20 min to obtain an oil phase. Water, ethanol, alkyl polysaccharide, ε-poly-L-lysine and transesterification catalyst are mixed, and reactive organic modified montmorillonite is added. The mixture is dispersed at 8000-10000 r / min for 5-15 min, and then sonicated at 200-300 W for 2-3 min to obtain an aqueous dispersion. A polyamine compound is added to the oil phase and mixed at 600-800 r / min for 2-6 min, with an epoxy equivalent / amine active hydrogen equivalent of 1.
04. The aqueous dispersion is then added to the oil phase over 8 min while being dispersed at 12000 r / min. After the addition is complete, a pre-reaction is performed, and then the mixture is cooled to 25℃ to obtain a prepolymer with a viscosity of 350-580 mPa·s at 25℃. S3: The plant fiber paper base is conditioned at 23℃ and 65%RH to achieve a moisture content of 8% to 15%. Then, it is vacuum impregnated. The paper base is removed and passed through a double roller once with a linear pressure of 0.2 to 0.8 MPa and a speed of 2 m / min. It is weighed and the final oven-dry weight gain is adjusted by adjusting the roller gap to achieve a final oven-dry weight gain of 22% to 28%, thus obtaining impregnated paper. S4: The impregnated paper after squeezing out the liquid is laid flat in a pre-drying equipment with solvent recovery and explosion-proof ventilation structure, and pre-dried at 60±5℃ and gauge pressure -0.060MPa. It is weighed every 5 minutes until the mass change does not exceed 0.5% for 5 consecutive minutes. Then the impregnated paper base is placed in a glass-ceramic pressing mold and subjected to microwave radiation. Then it is humidified at 23℃ and 50%RH for 48 hours to obtain the paper-plastic material for tabletop game packaging.
7. The method for preparing a PFAS-free biodegradable paper-plastic material for board game packaging according to claim 6, characterized in that, The preparation of montmorillonite dispersion in step S1 specifically involves adding sodium montmorillonite to deionized water, stirring at 600-800 r / min for 45-65 min, sonicating at 20 kHz, 450 W, 5s on / 5s off for 15 min, and keeping the system below 35°C to obtain the montmorillonite dispersion.
8. The method for preparing a PFAS-free biodegradable paper-plastic material for board game packaging according to claim 6, characterized in that, The pre-reaction described in step S2 specifically involves a pre-reaction at 40–50°C and 500–600 r / min for 10–20 min.
9. The method for preparing a PFAS-free biodegradable paper-plastic material for tabletop game packaging according to claim 6, characterized in that, The vacuum impregnation described in step S3 specifically involves completely immersing the paper base in the prepolymer and impregnating it under vacuum for 2 to 8 minutes at a gauge pressure of -0.060 to -0.095 MPa; then restoring it to normal pressure within 30 to 90 seconds and continuing to soak it for 1 to 5 minutes.
10. The method for preparing a PFAS-free biodegradable paper-plastic material for board game packaging according to claim 6, characterized in that, The microwave radiation described in step S4 specifically involves applying a surface pressure of 0.5–1.5 MPa, performing pulsed radiation with 2.45 GHz microwaves for 12 seconds on and 8 seconds off, with an effective absorption power density of 0.8–1.2 W / g, a cumulative on-time of 180–300 seconds, a core temperature of 110–120°C, and a temperature difference between the core and the surface of no more than 15°C. After stopping the microwave, the pressure is maintained for 3 minutes, and the core is demolded after the temperature drops below 70°C.
Citation Information
Patent Citations
High-performance fluoride-free oil proofing paper as well as preparation method and application thereof
CN110528332A
Preparation method of degradable coating high-barrier paper
CN113638267A
